Panel 8: Complications and Sequelae. (27th March 2013) - Jung, Timothy T. K.; Alper, Cuneyt M.; Hellstrom, Sten O.; Hunter, Lisa L.; Casselbrant, Margaretha L.; Groth, Anita; Kemaloglu, Yusuf K.; Kim, Sang Gyoon; Lim, David; Nittrouer, Susan; Park, Kee Hyun; Sabo, Diane; et al.
Abstract : Background and Objectives: Although serious complications of otitis media (OM) such as brain abscess are rare, sequelae of OM such as tympanic membrane perforation and atelectatic tympanic membrane are quite common. Inner ear sequelae can cause hearing loss and speech and language problems. The objectives of this article are to provide a state‐of‐the‐art review on recent articles on complications and sequelae of OM in different anatomic locations, from the tympanic membrane to intracranial sites, as well as hearing loss and speech and language development. Data Sources: Primarily PubMed supplemented by Ovid MEDLINE and the Cochrane Database. Review Methods: All types of articles related to OM complications and sequelae published in English between January 2007 and June 2011 were identified. A total of 127 relevant quality articles are summarized and included in this report. Results: Key findings are summarized based on the following major anatomic locations and categories: tympanic membrane; cholesteatoma; ossicular problems; mucosal sequelae; inner ear sequelae; speech and language development; extracranial areas, including mastoiditis and facial nerve paralysis; intracranial complications; and future research goals. New information and insights were gained to prevent complications and sequelae. Conclusion and Implications for Practice: Over the past 4 years, progress has been made in advancing the knowledge on the complications and sequelae of OM, which can be used to prevent and treat them effectively. Areas of potential future research have been identified and outlined.